Developing Interactive Multimedia In Animation Key To Improve The Spirit Of Student Learning Vocational High School - Pujawan, Kadek Agus Hendra (LPPM Undiksha, 2017)
This study was aimed to (1) Design and Implement Interactive Multimedia Development in Animation Key in Multimedia class XII SMK Negeri 1 Sawan; (2) Find out students responses and Achievment of Multimedia class XI toward Interactive Multimedia Development in animation Key. The types of research and development and using Dick and Carrey model, it involves Multimedia class XII SMK Negeri 1 Sawan in the academic year of 2014/2015. The source of data content expert and media expert are interview and questionnaire. Validity of interactive multimedia and student responses gained by using questionnaire, the data was analysed descriptive qualitatively and descriptive kuantitatively. The feedback of media expert then analysed thus, that media is valid and proper to be implemented in teaching learning process in the intened school. The results of studentâs responses data shows that the presentase of student who gave very positives responses was 64,2%, presentase of student who gave positive responses was 35,8 %, and none student to gave doubt responses, negative or even very negative response, the average scor was 43,69. That scor shows that studentâ response toward material development was in very positive chategory.